An Inter-temporal Analysis of Operational Efficiency of Oil Firms: Further Evidence from Nigeria - Oke, David Mautin; Kareem, Salami Dada (International Journal of Energy Economics and Policy, 2013)
There have been growing needs to investigate oil and gas firms more closely due to their corporate scandals. Globally, oil firm managements have become more risk intolerant. They are sometimes under pressure to deliver results within a short time, which often negatively affect their ability to undertake risky ventures that are rewarding.Applying the Data Envelopment Analysis, this paper shows a high level of technical operational inefficiency of 0.51 in Nigerian oil industry over the period 2006-2009. The fall in technical efficiency of the oil firms in 2009 might be attributed to the banking crisis in Nigeria in 2009 that affected financial operations of some oil firms that relied on banking credits for running their business, and the fall in global oil prices relative to mid 2008. Keywords: Operational efficiency; oil firms; data envelopment analysis JEL Classifications: C14; H21; Q49